Sea Surface Temperature and Sea Level Rise Impact on Coastal Dynamics in Makassar, South Sulawesi, Indonesia - Nurbaeti,; Saepuloh, Asep; Azikin, Busthan; Rachmayani, Rima (International Journal of Marine Engineering Innovation and Research, 2025)
Makassar City in South Sulawesi (Indonesia) is located at a low elevation of about 0-25 meters, while the coastal area is only 1-5 meters above sea level and is composed of alluvial deposits. The western boundary is directly adjacent to the Makassar Strait. These conditions make Makassar City highly vulnerable to the impacts of ocean dynamics and coastline changes caused by erosion or sedimentation, posing significant threats to infrastructure and livelihoods. This study aims to quantify sea-level changes that potentially cause coastal disasters in Makassar by detecting temporal variations in sea surface temperature (SST) and coastline changes. This study utilized remote sensing technology from AQUA MODIS, Landsat 7 ETM+, and Landsat 8 OLI/TIRS. The in-situ sea temperature measurements were conducted using a conductivity-temperature-depth (CTD) hydrographic device. In addition, the coastline verification was performed using a traverse of a global positioning system (GPS) device. Image processing was done using the SST extraction and band ratio methods to detect sea surface temperatures and coastlines, respectively. According to the AQUA MODIS data, the maximum SST increased from 28.84°C to 30.69°C from 2004 to 2024 with the highest temperature occured in 2024. The increase of SST agreed to the increase of sea level and coastlines. The evidence of the coastline changes presented by sedimentation and erosion is about 3.47 hectares and 32.89 hectares, respectively. The geological factors that play a role in coastal sedimentation and erosion originate from river sedimentation supply and increased sea level.